Dobro moralne w praktyce zawodu nauczycielskiego - Ślipko SJ, ks. Tadeusz (Annales. Etyka w Życiu Gospodarczym, 2010)
The idea of the moral good is considered a desirable and appreciated real existence. With reference to teachers it constitutes a personal pattern of judicious acting. Their special task is not only to teach necessary knowledge to students but also to instil moral conduct in them i.e. to form ‘a correct character’. This notion was present at the beginning of the 20th century and is also reflected in Archbishop Józef Bilczewski’s letter ‘The Character’ (1920). The ideas presented there remain still valid also in the present historic moment of the nation.